2009
DOI: 10.1371/journal.pone.0008130
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Detergent-Insoluble Proteins in ALS Indicates a Causal Link between Nitrative Stress and Aggregation in Pathogenesis

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a progressive and fatal motor neuron disease, and protein aggregation has been proposed as a possible pathogenetic mechanism. However, the aggregate protein constituents are poorly characterized so knowledge on the role of aggregation in pathogenesis is limited.Methodology/Principal FindingsWe carried out a proteomic analysis of the protein composition of the insoluble fraction, as a model of protein aggregates, from familial ALS (fALS) mouse model at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
92
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 68 publications
(84 reference statements)
9
92
1
Order By: Relevance
“…Insoluble aggregates of GAPDH are found in many diseases (11)(12)(13)(14)(15)(16)(17)(18)(19). No prior study has ascribed a structural/functional role for Met-46 in GAPDH biology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insoluble aggregates of GAPDH are found in many diseases (11)(12)(13)(14)(15)(16)(17)(18)(19). No prior study has ascribed a structural/functional role for Met-46 in GAPDH biology.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies show that GAPDH converts from its native soluble state into a non-native high molecular weight insoluble state during disease (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). For instance, insoluble aggregates of GAPDH have been observed in the affected tissues of patients with Alzheimer disease (13) and alcoholic liver cirrhosis (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the sites of Eno1 nitration at Tyr (43) is also a target of phosphorylation, suggesting the nitration of the protein may affect the function of the proteins as discussed earlier. In addition, a study by Basso et al (32) showed that nitration of the proteins play an important role in the aggregation of proteins, suggesting that oxidation/nitration has a key role in aggregation. All these data together may indicate that multiple oxidative modifications extensively and simultaneously affect certain proteins, inducing misfolding and finally aggregation.…”
Section: G93amentioning
confidence: 99%
“…As such, reducing NO helps prevent neuronal death in these circumstances, again linking elevated NO to neurodegeneration. In models of amyotrophic lateral sclerosis, nitrosative stress increases the likelihood of protein aggregation for key proteins [115] , neuronal loss in the 6-OHDA-lesioned rat model of PD [84] .…”
Section: Conclusion and Discussionmentioning
confidence: 99%